Evaluation of bacteriostatic effect of rosemary and oregano essential oil against a non-pathogenic surrogate of salmonella spp. (E. coli ATCC 9637) - Magtalas, Theodore John C.; Anapi, Gerieka R. (Quezon City University of the Philippines Diliman, 2024)
Food preservation and safety is a paramount to our continued survival in good health. Bacterial growth in food products is a significant obstacle to achieving food safety. Such growth can lead to spoilage and food-borne illnesses, which becomes a safety risk to consumers. As such, managing bacterial growth in food is essential to maintaining food quality and safety. The use of food additives is one answer raised to address this problem. However, some synthetic antimicrobial additives pose minor to serious health risks to consumers. Natural antimicrobial additives are potential alternatives to synthetic additives that are able to control microbial growth without significant health risks. This study evaluated the bacteriostatic effect of rosemary (REO) and oregano essential oil (OEO) against E. coli ATCC 9637, a non-pathogenic surrogate of Salmonella spp. in culture and in raw chicken breast. A final concentration of 1.5% REO and 0.15% OEO were added to cultures of E. coli ATCC 9637 and growth rate was evaluated. Raw chicken breast pieces were dipped in E. coli ATCC 9637 culture prior to being dipped in 1.5% REO and 0.15% OEO. Chicken samples were then taken at two day intervals and growth of E. coli ATCC 9637 was analyzed. No growth was observed in culture after a 24 hr incubation period. Chicken samples treated with 1.5% REO resulted in a 0.69 log reduction compared to the positive control, while those treated with 0.15% OEO resulted in a 0.31 log reduction (p < 0.05). This shows that REO and OEO are effective against E. coli ATCC 9637 and have promise as natural antimicrobial agents.
In partial fulfillment for the Degree of Bachelor of Science in Food Techonology
Thesis
Keywords: Essences and essential oils; Rosemary; Oregano; Bacteriostatic effect